Implementation of STEAM-Based Mathematics Learning at Junior High School during the Pandemic - Ika Indah Pratiwi; Rita Pramujiyanti Khotimah (STAI Hubbulwathan Duri, 2022)
STEAM approach is one of the learning strategies that connect between fields of science with the aim of training critical, creative, innovative thinking skills and student problem-solving skills. The purpose of this study is to describe the implementation of STEAM-based mathematics learning at one of the junior high schools in Surakarta. This type of research is qualitative descriptive with the subjects were 16 students of class IX and one STEAM learning teacher. Data collection techniques used are interviews, observations, and documentation. The process of data analysing is through data reduction techniques, data presentation, and conclusion drawing. The results showed that the implementation of STEAM-based mathematics learning implemented a shift system where the number of student attendance was only 50% of the total number of students in the class. The learning process is using the Project Based Learning model because mathematics learning in one of the junior high schools in Surakarta is implemented into the creation of a STEAM project with group discussion methods. STEAM-based mathematics learning covers aspects of STEAM. Science is associated with everyday problems such as applying pascal’s law to elevators. Technology implemented on the use of tools and materials. Engineering is associated with the ability of students in solving problems, one of which is in assembling a project. Art includes the ability of students to create a project. Mathematics is related to calculating and measuring a project. As for the problems experienced by teachers and students during the pandemic of the new normal era, is the estimated time given to complete a project.